Comparison Of The Effectiveness Of Grape Seed And Onion Extract In Healing Cut Wounds In Wistar Rats - Debora Helena Siahaan; Oliviti Natali; Djohan Djohan (Green Publisher Indonesia, 2024)
In healing cut wounds, generally many use drugs with chemicals, the use of chemicals in wound healing has a lot of negative impacts, therefore it is necessary to conduct further research on the benefits of natural ingredients such as plants to treat cut wounds, some of the advantages of using medicinal plants include relatively safer, easy to obtain, cheap, does not cause resistance, and relatively harmless to the surrounding environment or the mixture between the plants, which has been used for treatment for generations. One way to treat cut wounds is to use herbal plants because they are cheaper, easier to get, and have low side effects. Compounds that play a role in the healing process of cut wounds include flavonoids, saponins, tannins, polyphenols, and essential oils. One of the plants that has health benefits is grapes. The purpose of this study is to find out the comparison of the effectiveness of grape seeds and onion extract in healing cut wounds in wistar rats. The type of research used in this study is experimental research with a true experimental method with a post-test only control group design pattern. The sample to be used in this study is 24 rats divided into 4 groups so that each group contains 6 rats. Data analysis uses the One-Way ANOVA test. The results showed that shallot gel extract had a significant effect on the percentage of reduction in incision length.